Intraoperative Blood Loss & operating time in Tonsillectomy: Is Electrodissection Better? - Guragain, R; Bhusal, CL; Adhikari, P; Pokharel, R (Nepalese Journal of ENT Head and Neck Surgery, 2011)
DOI: 10.3126/njenthns.v1i1.4728 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.6-7